The synergistic effect of the carbon shell pore volume and core Pd size of Pd@hollow@C-X for the synthesis of H2O2. (11th January 2021) - Zhang, Jiesong; Liu, Peng; Shi, Yongyong; Fu, Chengbing; Lin, Qian; Liu, Fei; Pan, Hongyan
Abstract : Yolk–shell Pd@hollow@C- X ( X = 1.5, 3.2, 4.5 and 6) catalysts with Pd as the core and porous carbon as the shell were prepared via the inverse microemulsion method. Abstract : Yolk–shell Pd@hollow@C- X ( X = 1.5, 3.2, 4.5 and 6) catalysts with Pd as the core and porous carbon as the shell were prepared via the inverse microemulsion method. The carbon shell pore volume and core Pd size were controlled by varying the NH3 ·H2 O amount. Results showed that with an increase in the NH3 ·H2 O amount, the average particle size of Pd nanoparticles and shell pore volume decreased first and then increased, and when the NH3 ·H2 O amount was 3.2 ml, the as-prepared Pd@hollow@C-3.2 catalyst had the smallest Pd particle size and largest shell pore volume as 5.54 ± 1.37 nm and 0.12 m 3 g −1, respectively. The smaller Pd particle size can provide more active sites for the adsorption and reaction of H2 and O2 reactants, and the larger shell pore volume is beneficial for their adsorption. This makes the Pd@hollow@C-3.2 catalyst possess the highest selectivity and productivity in the H2 O2 synthesis, reaching 93% and 3197 mmol (gPd −1 h −1 ) −1, respectively, at 1 bar.